Uterine artery pseudoaneurysm presenting with subcutaneous hematoma and vaginal bleeding following cesarean delivery - Hatem Frikha; Haithem Aloui; Abir Karoui; Rami Hamami; Sana Menjli; Hassine Saber Abouda; Mohamed Badis Chanoufi (Elsevier, 2024)
We present a rare case of uterine artery pseudoaneurysm (UAP) following an emergency cesarean section, which led to severe vaginal bleeding and subcutaneous hematoma. The patient, a 40-year-old woman with no history of hemophilia or hemostasis disorders, presented with sudden profuse vaginal bleeding and multiple subcutaneous hematomas at the site of the cesarean scar ten days postoperation. Ultrasound and CT scan confirmed the presence of a pseudoaneurysm in the right uterine artery. Due to the unavailability of radiological embolization, surgical ligation of the right internal iliac artery was performed. Postoperative follow-up showed successful resolution of the pseudoaneurysm and cessation of bleeding. This case highlights the importance of considering UAP in the differential diagnosis of postpartum hemorrhage and demonstrates the efficacy of surgical intervention when embolization is not available.